Conversation with Stephen Prothero. (October 2016) - Prothero, Stephen; Gallagher, Eugene V.; Pearson, Thomas; Robinson, Joanne; Stortz, Martha E.
Abstract: This interview was recorded and transcribed in November 2015. Stephen Prothero is a professor of religious studies at Boston University, where he has taught since 1996. His publications include several that directly address teaching about religion, most notably Religious Literacy: What Every American Needs to Know – and Doesn't, which made an argument regarding K‐12 education. In this manuscript he pulls the conversation into his own undergraduate classrooms – providing a vivid glimpse of his teaching practices, including how he conducts large lecture classes and seminars, how he works with teaching assistants, and how he conducts discussions even in very large courses. He also shares his broader reflections on the nature and importance of religious literacy and its place in American education.